Plan de negocios para la creación de un SPA en el corregimiento de Minca en la ciudad de Santa Marta (2022)
The present work presents the Business Plan for the creation of a Spa in the Corregimiento of Minca, in the city of Santa Marta, whose main objective is to evaluate the feasibility of creating a space for relaxation and personal care for both the inhabitants of Minca and for the tourists. The research is developed under a quantitative approach with a type of inductive, non-experimental method, with data collection through surveys through the formulation of questionnaires, using as a sample the population whose ages range between 18 to 70 years, of a group between 80 and 100 people from the area as well as tourists, obtaining the data for the bases of the business proposal from a primary source. The study is structured in its first part based on research methodology to then propose the business idea with the premises obtained in the market study and the evaluation of the services provided by the competition. To support this Business Plan, an economic study was developed, where macroeconomic and market variables that affect the business were taken into account. Developing in this section, the accounting and financial bases of the Business Plan for the creation of the Spa. In this sense, the sales projections are developed, establishing the different services that are to be developed in the spa and the inherent costs of the process of the different activities that will be carried out, placing it in what will be its productive development and start-up. . And finally, the profitability indicators of the Investment, Balance Point, Net Present Value (NPV) and the Internal Rate of Return (IRR) were applied, essential to determine the viability of the investment, for which, it constitutes a reliable source. for investors.